Machine for making jam - Shamsuddin, Rosnah (2010)
A Jam Maker intended for small scale industry was designed as a batch process and divided into two main fuctions, heating and mixing process. The cooking bowl was designed in a cylindrical shape and a medium size, equipped with a flexible paddle mixer for homogeneous. The cooking bowl consist of two layers with different function. The inside surface is for holding of mixture or cooking process, the middle layer is for the heating coil and the external layer for the insulation to avoid heat loss. The function of using a paddle of agitation is to achieve a uniform distribution of mixing ingredient. The paddle made from combination of stainless steel and Teflon, which is more suitable for food uses, avoid eroding of cooking bowl surface and maintain at high temperature.